Análisis de la gestión del capital del trabajo y el desempeño financiero de las empresas de transporte urbano y sub urbano de la provincia de Cotopaxi por el periodo 2018 – 2021. - Franco Calle, Johel Alexander (2023)
The objective of this research project was to analyze whether the management of working capital affects the financial performance of urban and sub-urban transport companies in the Cotopaxi province for the period 2018-2021, through a diagnosis of the financial situation of the companies, analyzed through indicators that measure working capital management (net working capital, income level, turnover of accounts receivable, turnover of accounts payable, current passive and total passive ratio, and the impact on the financial burden ) and the indices that measure profitability such as (return on assets, return on equity and return on sales) whose results were reflected in statistics such as the minimum, maximum, mean and standard deviation. For this, a database was formulated with the financial information of 23 companies and during the exploratory analysis it was determined that some companies didn’t have the necessary information for the execution of the study, so the investigation was carried out with 7 companies and to calculate. For the statistical model, a company was taken as a reference which had the most representative data in its financial statements (Intra-cantonal passenger transport company Citibus S.A), the model consists of the following steps: Preparation of a Pearson correlation matrix, determinants of the total variance explained, extraction of components and finally the determination of the number of components. Through the result of the statistical process, the alternative hypothesis was rejected, determining that working capital management doesn’t have a significant impact on the financial performance of the transport sector, because there weren’t high correlation values between the two variables, no correlation index was found greater than 0.6 and later the extraction of principal components was explained with a variance greater than 90%, which means that most of the data were explained in the dimensionality reduction. And finally, the component extraction indices don’t yield values close to 1 and -1, thus demonstrating that the variables don’t have a significant impact, due to the fact that the vast majority of transport companies operate as intermediaries and generate income through the contributions made by partners through the provision of their services to the public.